Pengaruh Gaya Kepemimpinan, Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan - Eka Wulandari; Iin Emy Prastiwi; Abdul Haris Romdhoni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2021)
This study aims to examine and analyze the influence of leadership style, work motivation, work discipline on the performance of the employees of PT Hermosa Garment International. This research uses a quantitative descriptive approach. The technique collected is in the form of primary data through a questionnaire distributed to respondents called a questionnaire. Data collection techniques using purposive sampling technique which is a sampling technique with certain considerations, namely using certain criteria such as employees who have worked more than 1 year, this research was conducted by distributing questionnaires and carried out by 39 employees of 214 employees at PT Hermosa Garment International. From the results of the study that the leadership style variable does not significantly influence employee performance, the results of the multiple regression equation obtained a value of 0.108, with a t value of 0.887 smaller than t table 2.03011 and a Sig value of 0.381 greater than 0.05, then Ha rejected. Work motivation variable does not significantly influence employee performance, namely the value of the multiple regression equation results in a value of 0.153, with a t value of 1.437 smaller than t table 2.03011 and a Sig value of 0.160 greater than 0.05, then Ha is rejected. Work discipline variables have a significant effect on employee performance, namely the value of the results of the multiple regression equation obtained a value of 0.582, with a t value of 3.727 greater than t table 2.03011 and a Sig value of 0.001 smaller than 0.05, then Ha is accepted. Leadership style, work motivation and work discipline together (simultaneously) significantly influence the performance of employees at PT Hermosa Garment International.